ANTISIPASI LONGSORAN KEGIATAN PENAMBANGAN PASIR DALAM RANGKA PEMELIHARAAN SUNGAI GENDOL - Rofa Dzulfikri Bulopa; Dwi Herniti (ReTII, 2022)
The activity of sand mining activities are still not safety in regulations. Until now the actual implementation of sand mining activities in Mount Merapi has not been as expected. Mining activities caused negative impacts as environmental damage as well as vertical and horizontal conflicts. The failure of implementing the policy is due to the lack of awareness stakeholders on environmental sustainability and complying with regulations. Weak supervision, control and development of mining activities and the law has not been enforced. Differences in perceptions about the management of Mount Merapi’s sand are the root of the prolonged conflict in Merapi’s sand mining activities. Therefore, the author has the initiative to carry out community service activities with the theme of anticipating avalanches, considering mining in the Gendol river and very dangerous. The method used for this community service is a descriptive analysis method, we do by interviewing to the miners and the owner. So that is produced that mining activities must be carried out with good mining practice to avoid of landslides that always lurk the miners in the Gendol River, because sand mining activities in the Gendol River if not carried out with good mining practise potential high risk of landslide.